Multivariate Regression Analysis of the Impact of Open Market Share Repurchase Activity on the Malaysian Market - Sohail Ahmed (Information Management and Business Review, 2024)
This research thesis revolves around the need to understand the relationship between share repurchases and the share price behavior of companies listed on Bursa Malaysia on a more recent basis given the economic stability in Malaysia and throughout the world from 2017 to 2021. It started in the West and reached maturity in the 1980s in the United States, but it only began in Malaysia in the 1990s. The studies of share repurchase are still considered an infant in Malaysia as in other countries throughout the world, companies pursue share repurchases for several reasons mainly to signal undervaluation, reward shareholders, defend against the takeover, utilize financial resources efficiently, and many more motives that are interesting for researchers to look at. Unlike other studies that look at announcement dates, since an announcement does not mean the companies will implement the transactions, this research is important since it looks at and analyzes the actual effective repurchase day done by established firms which is are most crucial aspect in analyzing the consequences and the results are that it shows positive abnormal mean returns for most of the companies. Event study methodology was used since this is the best empirical research method and as empirical evidence to analyze abnormal returns from all the other studies. The days observed are 120 days before and after the announcement. Returns for the estimation window, event window (repurchase day), and post-event window were analyzed to see the effects of price movement on repurchase activities at Bursa Malaysia (BSKL).